PID control: Resilience with respect to controller implementation - Alfaro, V. M.; Vilanova, R. (Frontiers in Control Engineering, 2022)
One of the major drawbacks of the basic parallel formulations of the PID controller are the effects of proportional and derivative kick. In order to minimise these effects, modified forms of parallel controller structures such as PI-D and I-PD are usually considered in practice. In addition, there is the usual servo/regulation tradeoff regarding the closed-loop control system operation. Appropriate tuning is needed for each situation. One way of making explicit focus on load disturbance is by appropriate selection of the controller equation. There is therefore a gap between the conception of a tuning rule and its final application that may need deployment on different controller equations. There is no danger when we go from PI-D to I-PD as we just change reference processing. However, there will be a loose of performance. The potential loose of performance depending of the final controller equations used, motivates the authors to introduce the idea of resilient PID tuning: minimise the effects of changing the controller equation on the achieved performance/robustness. This can be seen as a complement to the, today, well known controller fragility concept. On the basis of this scenario, this paper motivates an analysis of a tuning rule from such point of view and also emphasising the benefits that a better process model may provide on such respect.